Cook organically - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Pacific s Cook Islands are getting ready to seize the region s organic fruit market which includes New Zealand and Australia. Standards and certification procedures are in place, and production has started with Noni (Morinda citrifolia); other...